PHYSIOLOGIC AND SANITARY QUALITY OF CASTOR BEAN SEEDS UNDER DIFFERENT CHEMICAL TREATMENTS - Tropaldi, Leandro (2010)
The use of fungicides for treating seeds has become an essential measure in the control of pathogens. However, the effectiveness of many products is not well-known to some crops. The objective of this research was to evaluate the effect of different doses of carbendazin and carboxin + thiram fungicides for controlling pathogens and their interference on the physiologic quality of castor bean seeds. The test consisted of the following treatments (g i.a./100 kg of seeds): carbendazin (15, 30, and 60), carboxin + thiram (25 + 25, 50 + 50, and 100 + 100), formol 0.15% (v/v), and control (distilled water). The physiologic quality of the seeds was determined by germination, first counting, field emergence, speed emergence index, length, fresh and dry weight of the aerial part, and electrical conductivity. There were no statistical differences for germination and fresh and dry matter index. The treatment with formol provided lower values for first counting and field emergence. Seeds treated with fungicides presented higher values for electrical conductivity, but did not differ, statistically, among themselves. The fungi Cladosporium spp.; Bipolaris spp.; Curvularia spp.; Aspergillus flavus; Aspergillus niger; Rhizopus sp.; Penicillium sp.; Rhizoctonia sp.; Verticillium sp.; Fusarium sp.; Arthrobotrys sp.; and Epicocum sp. were identified. All tested products, independently of the dose, provided efficient control for pathogens. KEY-WORDS: Ricinus communis L.; seeds pathogens; carbendazim; carboxim; thiram.